Poverty governance system in the public sector administration affairs in Malaysia - Zabidi, Nadirah; Ismail, Mohd Mahadee; Adnan, Zatul Himmah; Mohd Zain, Mohd Izani (Human Resource Management Academic Research Society, 2022)
This manuscript attempts to determine the concept of governance, the practice of the poverty governance system and the good governance approaches that the public sector administration in Malaysia is applying. The paper is based heavily on the literature review and report from the Economic Planning Unit and National Audit Department. Empirical evidence has shown the public sector administration has been practicing good governance based on work ethics principles initiated by the National Institute of Public Administration. The Department of Social Welfare is selected as an institution that actively manages and administers any issue related to poverty and welfare services. However, the criticisms and complaints towards the public sector services, especially regarding working practices efficiency, remain to be heard. This has been highlighted as the biggest challenge to the public sector. This article implies the issue of poverty will be administered in a well-managed environment along with the good governance approaches but applying ‘good enough governance’ can be considered a realistic target for the governance system in the public sector. The main viewpoint is the quality and sustainability of public sector services are much more important rather than achieving good governance in its totality.